The Making and Unmaking of a Colonial Subject: Othello - Ana María Manzanas Calvo (Miscelánea: A Journal of English and American Studies, 1996)
Taking as a starting point the fact that Othello’s colour is politically and ideologically relevant in the development of the play, this article offers a reading of Othello as a tragedy of race. The article reviews key texts where the stereotype of the black man as a “pagan conjurer” of beastly living and monstrous sexuality crystallized, and traces the presence of the stereotype throughout the play. Othello’s condition as a black man—whatever shade of blackness he was—is further complicated by his condition as a colonial subject who wishes to adopt western culture. The play dramatizes the apparently unlimited possibilities of self-fashioning available to man in the Renaissance, only to deconstruct this optimistic self-fashioning or self-creation when race issues come into play. It is Iago’s exploitation of the politics of colour and of Othello’s double nature (proper to a colonial subject) that brings about Othello’s downfall.